(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this chapter, a facile green process was developed for the synthesis of AgNPs - rGO composite by using Citrullus colocynthis leaf extract as a reducing and stabilizing agent. The morphology and microstructure of the magnetic nanocomposite was examined by FTIR, XRD, UV-VISIBLE and SEM. Here, the green synthesized nanocomposite display remarkable effective removal of Methylene Blue (MB) from aqueous solution, showing a maximum adsorption capacity reached up to 146.43 mg L-1 within only 30 minutes at room temperature.The kinetics, isotherms and thermodynamics of the adsorption of MB have been studied at various experimental conditions (initial dye concentration of MB, adsorbent dosage, contact time and temperature). Adsorption kinetics and the equilibrium adsorption isotherm were found to follow a pseudo-second orderkinetic model and Langmuir isotherm, respectively. The thermodynamic parameters indicated that the adsorption was spontaneous, favorable, andendothermic in nature. Moreover, AgNPs - rGO was very stable and can be readilyreuse by washing with water. Therefore we believed that the prepared nanocomposite as a very good greenadsorbent for eliminating MB pollutant from aqueous solution